Embracing scepticism as a non-physical form of redundancy: lessons learnt from the UK blood supply chain - Lusiantoro, Luluk; Yates, Nicky (Taylor & Francis, 2023)
This paper seeks to understand how supply chain actors demonstrate scepticism as a non-physical form of redundancy to maintain supply chain resilience. It provides lessons learnt from three case studies of dyadic blood supply chains involving three blood centres and twelve hospitals in England. This paper identifies three key elements of scepticism, namely information duplication, warranting, and cross-evaluation. These elements act as preventive mechanisms, avoiding the unwanted consequences of routine behaviour, and averting mindless actions resulting from reactive operations. We argue that scepticism can be adopted as a complement to supply chain redundancy practices, increasing the robustness and agility of supply chain operations, and therefore enhancing supply chain resilience. To the best of our knowledge, this is the first paper to address the notion of scepticism, emphasizing the pivotal role of human behaviour in the supply chain resilience literature. Despite its specific context, the findings could potentially be applied in other industries.
Keywords: disruption; scepticism; information duplication; warranting; cross-evaluation; preventive mechanism; mindful action